2019
DOI: 10.1002/ptr.6430
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin reduces TNF‐α‐induced mesangial cell proliferation and inhibits PTX3 production: Involvement of NF‐κB signaling pathway

Abstract: Lupus nephritis (LN) is an autoimmune disease caused by systemic lupus erythematosus. Excessive proliferation of mesangial cells is one of the most serious pathological manifestations of LN. In addition, the expression of PTX3 is elevated in the serum of patients with LN. Quercetin has good anti‐inflammatory effects and immunomodulatory activities. In this study, the result of MTT indicated that quercetin treatment alleviated the excessive proliferation of mesangial cells. ELISA and immunofluorescence experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Therefore, MG132 and other proteasome inhibitors are usually used to inhibit protein degradation by the UPS to better detect the ubiquitination signal. However, PTX3 is generated by the NF‐κB pathway, 35 and proteasome inhibitors such as MG132 and MG101 significantly promote IκBα accumulation and inhibit the NF‐κB pathway 36 . We confirmed that MG132 and MG101 substantially inhibit PTX3 expression, and we therefore transfected HA‐UBB into MSCs in an attempt to increase the ubiquitination of PTX3 for better detection.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Therefore, MG132 and other proteasome inhibitors are usually used to inhibit protein degradation by the UPS to better detect the ubiquitination signal. However, PTX3 is generated by the NF‐κB pathway, 35 and proteasome inhibitors such as MG132 and MG101 significantly promote IκBα accumulation and inhibit the NF‐κB pathway 36 . We confirmed that MG132 and MG101 substantially inhibit PTX3 expression, and we therefore transfected HA‐UBB into MSCs in an attempt to increase the ubiquitination of PTX3 for better detection.…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, we detected the level of ubiquitinated PTX3 in HDMSCs and ASMSCs. PTX3 is generated by the NF‐κB pathway, 35 and proteasome inhibitors inhibit the NF‐κB pathway 36 . We initially confirmed that MG132 and MG101 substantially inhibited endogenous PTX3 expression (Supplementary Figure S2D).…”
Section: Resultsmentioning
confidence: 65%
“…For the co-infection of SARS-COV-2 and DENV, firstly, quercetin has a wide range of antiviral properties and can interfere with the virulence of pathogens with multiple steps [ 63 ]. Secondly, quercetin, an anti-inflammatory component, is able to decrease the inflammatory response via dose-dependently inhibiting the NF-κB signaling pathway and effectively reduces the level of inflammatory factors TNF-α, IL-6 and IL-17 [ 62 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…33 Studies have shown quercetin also exhibiting anti-inflammatory properties, [34][35][36] which could help mitigate the inflammatory response of cytokine and/or bradykinin storms provoked by COVID-19. A wide range of anti-viral/immunity benefits of quercetin have been identified, [37][38][39][40][41] as well as other health benefits that may address some comorbidities of COVID-19 [42][43][44] and some of its sequelae. 44,45 Role of vitamin C. Effects of vitamin C on the immune system (e.g., possible enhancement of activity of NK cells and of other effectors of immunity mechanisms) are well documented.…”
Section: Role Of Zincmentioning
confidence: 99%